2005
DOI: 10.1080/14034940510005752
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in leisure-time and risk of cancer: 14-year follow-up of 28,000 Danish men and women

Abstract: Generally, there were no, or only weakly, inverse associations between physical activity in leisure time and incidence of cancer, except for cancer of the ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
91
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 28 publications
5
91
2
Order By: Relevance
“…All studies adjusted for age and parity and most also adjusted for oral contraceptive use and BMI. Excluding studies that did not adjust for oral contraceptive use (15,22,30,34) and BMI (18,22,30,32) resulted in pooled estimates of 0.83 (95% CI, 0.80-0.86) and 0.81 (95% CI, 0.76-0.86), respectively, with no significant heterogeneity. The funnel plot of the effect estimates for the risk of ovarian cancer related to recreational physical activity was close to symmetrical, suggesting that there was no appreciable publication bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All studies adjusted for age and parity and most also adjusted for oral contraceptive use and BMI. Excluding studies that did not adjust for oral contraceptive use (15,22,30,34) and BMI (18,22,30,32) resulted in pooled estimates of 0.83 (95% CI, 0.80-0.86) and 0.81 (95% CI, 0.76-0.86), respectively, with no significant heterogeneity. The funnel plot of the effect estimates for the risk of ovarian cancer related to recreational physical activity was close to symmetrical, suggesting that there was no appreciable publication bias.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of the 16 studies assessed recreational physical activity [six case-control studies (15)(16)(17)(34)(35)(36) and six cohort studies (18,22,27,29,30,32)] and all presented risk estimates permitting meta-analysis together with the results of the current study. These studies are summarized in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some dietary behaviours, like drinking coffee, adding salt at the table, salted foods, meal frequency and cooking procedures, have not been included in dietary patterns, although they have been associated with the development of chronic diseases, like cancer. Specifically, epidemiological studies have shown that high intake of calcium and vitamin D (11,12) seems to have a protective effect on CRC risk and coffee intake (13)(14)(15) a conflicting effect, while frequent meals (16,17) and systematic physical activity (18,19) probably have modest protective effect. Added table salt or salted foods have been highly correlated with gastric cancer, but not with CRC.…”
mentioning
confidence: 99%